Insects diversity in lima bean (Phaseolus lunatus) - YAYAN SANJAYA; WIWIN SETIAWATI (Society for Indonesian Biodiversity, 2005)
Lima bean (Phaseolus lunatus) is a vegetable which usually made as a home yard plant for Indonesian people to fulfill their daily needs. This plant has not been produced in the large number by the farmer. So it is hard to find in the market. Lima bean is light by many kind of insect. Inventory, identification and the study of insect taxon to this plant is being done to collect some information about the insect who life in the plant. The research was done in Balitsa experiment garden in the district of Lembang in Bandung regency on November 2003- February 2004, the experiment start at 4 weeks age, at the height of 1260 m over the sea level. The observation was made systematically by absolute method (D-vac macine) and relative method (sweeping net). The research so that there were 26 species of phytofagous insect, 9 species of predator insect, 6 species of parasitoid insect, 4 species of pollinator and 14 species of scavenger insect. According to the research the highest species number was got in the 8th week (3rd sampling), which had 27 variety of species, so the highest diversity was also got in this with 2,113 point. Aphididae and Cicadellidae was the most insect found in roay plant. The research also had high number of species insect so the diversity of insect and evenness become high. A community will have the high stability if it is a long with the high diversity. High evenness in community that has low species dominance and high species number of insect so the high of species richness.Key words: Phaseolus lunatus, diversity, dominance, evenness, richness